Sabbatical Leave Report Spring 2016: In Search of Mercy Ethnicity, Gender and Parochial Education in Washington Height, New York, and the Catechism of Bella Abzug and Audre Lorde - Kerr, Audrey Elisa (2016)
The purpose of this essay was to expand the ways critics think about Harlem and the Heights following the Great Depression by recovering women's creative responses to social and political angst in predominantly Catholic spaces.
Keywords: dept.eng; faculty_collection; sabbatical_report

Under the Red Dress - Mottola, Pat (Five Oaks Press, 2016)
Keywords: American poetry; dept.eng; faculty_collection

The Religion of Empire: Political Theology in Blake's Prophetic Symbolism - Rosso, G. A. (The Ohio State University Press, 2016)
The Religion of Empire: Political Theology in Blake's Prophetic Symbolism is the first full-length study devoted to interpreting Blake's three long poems, showing the ways in which the Bible, myth, and politics merge in his prophetic symbolism. In this book, G. A. Rosso examines the themes of empire and religion through the lens of one of Blake's most distinctive and puzzling images, Rahab, a figure that anchors an account of the development of Blake's political theology in the latter half of his career. Through the Rahab figure, Rosso argues, Blake interweaves the histories of religion and empire in a wide-ranging attack on the conceptual bases of British globalism in the long eighteenth century. This approach reveals the vast potential that the question of religion offers to a reconsideration of Blake's attitude to empire. The Religion of Empire also reevaluates Blake's relationship with Milton, whose influence Blake both affirms and contests in a unique appropriation of Milton's prophetic legacy. In this context, Rosso challenges recent views of Blake as complicit with the nationalism and sexism of his time, expanding the religion-empire nexus to include Blake's esoteric understanding of gender. Foregrounding the role of female characters in the longer prophecies, Rosso discloses the variegated and progressive nature of Blake's apocalyptic humanism.
SCSU Faculty Scholar Award
Keywords: Blake; William; 1757-1827; Criticism and interpretation; Blake; William; 1757-1827; History and criticism; Prophecies in literature; Political and social views; Blake; William; 1757-1827. Four Zoas; Blake; William; 1757-1827. Milton; Blake; William; 1757-1827. Jerusalem; Political theology; Epic poetry; English; Religion; Blake; William; 1757-1827; SCSU Faculty Scholar Award; award_winner; dept.eng

Hawthorne's Two Bodies: Politics and Aesthetics in Our Old Home - Baraw, C. (Literary Imagination, 2016)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Swinburne: Criticism as perversion - Fluhr, N. (Nineteenth Century Prose, 2016)
Keywords: dept.eng; ⛔ No DOI found

‘The Author Makes the Reader Acquainted with His Abode’: Hawthorne as Transatlantic Tour Guide in The Marble Faun and ‘The Old Manse’ - Baraw, Charles (Transatlantic Literature and Author Love in the Nineteenth Century, 2016)
Here the volume continues its reflections on Hawthorne’s career but turns to his place in the literature of ‘homes and haunts’, taking up the question of how literary geography and its localization of authors helped construct an authorial presence for Americans and a tangible transatlantic literary canon. (It turns out that having a home on the literary itinerary was crucial to nineteenth-century reception.) Baraw demonstrates that the poetics of literary tourism provided Hawthorne with both a means of self-canonization as a tourist attraction and a tool for cultivating the ideal ‘English’ reader for his books. This essay begins a strand of chapters related to literary tourism and the construction of international heritage landscapes.
Citation Key Alias: lens.org/027-169-429-746-184
Keywords: American Author; Authorial Persona; Direct Address; Tour Guide; Tourist Attraction; dept.eng

Pain as semiosomatic force: The disarticulation and rearticulation of subjectivity - Larocco, Steve (Subjectivity, 2016)
Scarry's (The Body in Pain: The Making and Unmaking of the World, Oxford, New York, 1985) broke crucial ground in examining the antagonisms between pain, embodiment and language, and the isolating effects of pain as experience. This paper submits Scarry's claim that extreme pain destroys language, evades mediation, and isolates the subject to critical scrutiny, arguing instead that pain is a semiosomatic force, a form of feeling generated by imperative information about embodiment (real or imaginary) that works to disarticulate and move the subject and the social environment. Pain is not predominantly antagonistic to language; rather, pain insists on signifying, with language being only one of its performative media. What pain resists is representation, not the informational force exerted through language and other semiotic forms. Rather than unmaking language, pain disarticulates and rearticulates subjectivity, refashioning interrelations between the body, subjectivity, others, and culture in ongoing processes of largely aversive impingement, embroiling subjectivity with the imperative directives of embodied vulnerability. © 2016 Macmillan Publishers Ltd.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-246-870-419-636 tex.type: [object Object]
Keywords: dept.eng; embodiment; pain; performativity; semiotics; subjectivity